Evaluating the risks of public health programs: Rational antibiotic use and antimicrobial resistance. (18th August 2019) - Rid, Annette; Littmann, Jasper; Buyx, Alena
Abstract: Existing ethical frameworks for public health provide insufficient guidance on how to evaluate the risks of public health programs that compromise the best clinical interests of present patients for the benefit of others. Given the relevant similarity of such programs to clinical research, we suggest that insights from the long‐standing debate about acceptable risk in clinical research can helpfully inform and guide the evaluation of risks posed by public health programs that compromise patients' best clinical interests. We discuss how lessons learned regarding the ethics of risk in one context can be fruitfully transferred to the other, using the example of a so‐called 'rational antibiotic use' guideline that limits antimicrobial prescribing in order to curb antimicrobial resistance.